High reliability of repeated short burst on-water rowing trials - Soper, C.; Hume, P.; Tonks, R. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Knowing the normal expected variation between repeated performance tests is essential for monitoring performance or studying the effect of an intervention. When multiple on-water rowing trials are required in a single rowing session or on a single day, shorter trials than the standard 2000 m rowing race must be used. No research has investigated the reliability of repeated short duration maximal effort on-water rowing trials. This study aimed to determine the expected normal variation in performance when elite level rowers` completed five 60 s `maximal effort trials. Two male and nine female NZ 2003 squad single scullers completed five 60 s time trials at a constant self-selected high intensity stroke rate following a 1000 m warm-up. The single scull was instrumented with a linear proximity transducer (applied force) on each oar and a rotatory potentiometer (oar angle). All equipment has previously been determined to be highly linear under static and dynamic laboratory testing. Using pair wise analysis between trials one to five, total propulsive force, peak propulsive force, angle at peak force, stroke length and oar angle at the catch and finish were all highly correlated (r > 0.90). The typical expected error was lowest for stroke length (1.2%, 95% CL = 0.08 - 2.2) and worst for peak propulsive force (4.9%, CL = 6.7 - 17.8).